Open innovation: reaching out to the grass roots through SMEs - exploring issues of opportunities and challenges to reach economic sustainability - Rahman, Hakikur (© 2016 IGI Global, 2018)
This book chapter was published in the IGI Global [ © 2016 IGI Global] and the definite version is available at : http://doi.org/10.4018/978-1-5225-0556-3.ch012 The Journal's website is at: https://www.igi-global.com/gateway/chapter/157810